Análisis digital. Una nueva técnica para la representación de funciones acotadas que, en un intervalo finito, satisfacen las condiciones de Dirichlet - Skliar, Osvaldo (2000)
A new technique is introduced for the approximation of any bounded function f(t) that satisfies Dirichlet's conditions in a finite interval, with a precision as high as wanted. Such approximation in obtained by adding n trains of square waves. (Generally, n increases with the desired level of precision.)